Getting to know the person behind the illness – the significance of interacting with patients hospitalised in forensic psychiatric settings. Issue 9 (21st March 2016) - Salzmann‐Erikson, Martin; Rydlo, Cecilia; Wiklund Gustin, Lena
Abstract : Aims and objectives: To describe what nurses want to accomplish in relationships with patients who are hospitalised in forensic psychiatric settings. Background: Relationships between staff and patients in forensic psychiatric settings should be grounded in trust and confidence, and the patients need opportunities for emotional reconciliation. However, relationships can be challenging for nurses, who sometimes distance themselves from patients' expressions of suffering. The role of forensic mental health nurses is nebulous, as are the prescriptives and the implementation of nursing practices. Design: Qualitative descriptive design. Methods: In‐depth interviews with five nurses who all work in forensic psychiatric settings. Results: We present a descriptive analysis of what nurses want to accomplish in relationships with patients who are hospitalised in forensic psychiatric settings. The results are presented in two main categories: (1) getting to know the person behind the illness and (2) making a difference. Conclusion: Care in forensic psychiatry needs to shift towards a more long‐term view of the role of nursing, focusing less on the traditional and stereotypical identity of the productive nurse and more on the care given when nurses slow down and take the time to see the patients as individuals. Establishing trusting relationships with patients in forensic psychiatric settings is viewed as a less oppressive way to control patients and guide them in directions that are preferable for the nurses and for the society. Relevance to clinical practice: Nurses may use simple strategies in their daily practice such as sitting on the sofa with patients to establish trust. We stress that nurses should abandon policing roles and custodial activities in favour of guiding principles that promote individual recovery, treatment and health‐promoting care.